The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13014-018-1026-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of particle radiotherapy for the re-irradiation of recurrent intracranial meningioma

Abstract: BackgroundWith the advance of modern irradiation techniques, the role of radiotherapy (RT) for intracranial meningioma has increased significantly throughout the past years. Despite that tumor’s generally favorable outcome with local control rates of up to 90% after ten years, progression after RT does occur. In those cases, re-irradiation is often difficult due to the limited radiation tolerance of the surrounding tissue. The aim of this analysis is to determine the value of particle therapy with its better d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 41 publications
(39 reference statements)
1
39
0
Order By: Relevance
“…The lower rate of radiographic radiation injury observed in the current study is consistent with the prevalence reported by the Heidelberg group for reRT with particle therapy [21] and the prevalence reported by colleagues in our institution who studied risk of temporal lobe necrosis for PBRT reRT of skull base head and neck cancers [32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The lower rate of radiographic radiation injury observed in the current study is consistent with the prevalence reported by the Heidelberg group for reRT with particle therapy [21] and the prevalence reported by colleagues in our institution who studied risk of temporal lobe necrosis for PBRT reRT of skull base head and neck cancers [32].…”
Section: Discussionsupporting
confidence: 92%
“…Our series is hypothesis generating for prognosticating the patients who might benefit most from PBRT: those with longer interval between prior RT and reRT and those with initially grade I tumors. The finding that grade I histology portends improved prognosis following reRT has been recapitulated in other small series [9,[21][22][23]. This consistent finding suggests that full-dose reRT is unlikely to be sufficient for durable long-term response in patients with grade II-III disease, and future prospective efforts may need to consider novel combinations of RT with systemic agents to overcome a relatively radioresistant histology.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Seven studies examining re-irradiation for recurrent disease were identified across five different subsites, [51][52][53][54][55][56][57] including a recent systematic review 58 of 16 studies across broad indications. The level and quality of evidence was low as the majority of studies are retrospective, with small sample size, limited follow-up duration and do not directly compare results to photon-based re-irradiation.…”
Section: Other Tumour Sitesmentioning
confidence: 99%
“…The potential for severe early and late side effects after CIR depends primarily on the location of the tumor. In particular, re-irradiation of tumors that have infiltrated the base of the skull result in higher doses applied to dose-limiting OAR, such as the brainstem and temporal lobes [22]. Furthermore, simultaneous systemic therapies lead to a significant increase in treatment-related toxicities [1,2].…”
Section: Discussionmentioning
confidence: 99%